Analisis Faktor-Faktor Yang Memengaruhi Tingkat Kesejahteraan Penduduk Di Kabupaten/Kota Provinsi Bali - Lumbanraja, Joanna Fransiska; Yuliarmi, Ni Nyoman; Pratiwi, Ida Ayu Meisthya; Saskara, Ida Ayu Dyastari (Peneliti.net, 2024)
The population welfare can be measured by the Human Development Index (HDI). The province of Bali continues to experience an increase in HDI from year to year. However, upon detailed examination of each regency and city within it, disparities can be observed, especially between the Sarbagita region and non-Sarbagita regions. This research aims to analyze the factors influencing the population welfare in regencies/cities of the Bali Province. An associative quantitative approach is employed by gathering data published by the Central Statistics Agency (BPS) and the Health Office of the Bali Province. The research method applied is panel data regression, involving a series of statistical tests such as the selection of panel data regression models followed by t-test, F-test, and R Square test. This data analysis is expected to provide a comprehensive understanding of the influence of population ratio to community health centers, maternal mortality rates, student-to-teacher ratio at the high school level, percentage of population aged 15 years and over who completed tertiary education, Gini ratio, and poverty depth index on the population welfare in the context of the Bali Province. The statistical tests conducted will provide validity to the relationship between the variables under investigation. The results of this research are expected to contribute to understanding the factors influencing the population welfare in the Bali.